Potencyand Geneticdiversity of Bali Cattle - Eko Handiwirawan; Subandriyo . (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2004)
Bali cattle are important indigenous cattle due to high population and wide spread in Indonesia. Increasing meat and cattle imports to fulfill the local demand should be able to motivate related parties to improve productivity of Indonesian cattle through good management, including Bali cattle. Several good characteristics are possessed by Bali cattle, particularly the adaptation capability in environment with poor feed quality and they possess good fertility. The government decision to determine Province of Bali is as a protected zone for other cattle breed in order to conserve Bali cattle is very reasonable considering that Indonesia is the gene center of Bali cattle and the first domestication place of Bali cattle . Genetic improvements ofBali cattle have been done at pure breed zone (Province of Bali) through selection and progeny testing at P3Bali and succeeds in obtaining cattle with good Estimated Breeding Value. Elite bulls obtained through the program are expected to be able to entirely improve Bali cattle in Indonesia through Artificial Insemination program. The improvement of genetic quality by crossing with Bos taurus and Bos indicus have been done at livestock sources regions and have been able to produce crossbred having good productivity as final stock. There is tendency to continuously improve the genetic composition ofBos taurus through artificial insemination at farmers level. The ideal genetic composition of crossbred needs to be evaluated to reach optimal genotype composition. Key words: Bali cattle, conservation, genetic improvement